Obstáculos à implementação da reforma gerencial: as organizações sociais - Alcoforado, Flávio Carneiro Guedes (2012)
The objective of this work is to investigate the obstacles to the implementation of the QuasiAutonomous non-Governmental Organizations model in Brazil, particularly in the Science and Technology field of the Federal Government, with the purpose of demonstrating that stipulated controls for managerial reform of Public Administration were added to classic controls already in use, creating an overlap of controls in the Quangos model, which now has to check results, adopt transparency and accountability mechanisms and also use classic controls of procedure stipulated by the theory of bureaucracy. To verify our hypothesis, we discussed the theory of bureaucracy, NPM and managerial theory of Public Administration, researched documents of the Ministry of Science and Technology, the Brazilian Federal Accountability Office and the legal and infra-legal norms related to the theme. Furthermore, we interviewed actors of the five Quangos related to the MCT and other actors which are important to the process of implementation of the Quangos model in the federal sphere. Our analysis demonstrated that managerial reform predicates applicable to the Quangos model have been used and the entities have reached satisfactory results regarding agility and management by results through contracts of management, but stipulated controls for the managerial model were added to classic controls, from the bureaucratic paradigm, already used in public administration organs.